Analysis of engineering invention competencies in standards and programmes of engineering universities; Procedia - Social and Behavioral Sciences; Vol. 171 : International Conference on Education & Educational Psychology - Zamyatina O. M. Oksana Mikhailovna; Minin M. G. Mikhail Grigoryevich; Denchuk D. S. Daria Sergeevna; Sadchenko V. O. Viktoriya Olegovna (2015, 2015)
Title screen